DESAIN PENGEMBANGAN E-MODUL PEMBELAJARAN TEKS DEBAT DI SMA KELAS X - Purwati Zisca Diana (Lembaga Kajian Nusantara Raya (LK Nura), 2022)
This development research is motivated by the problem of using electronic media, namely e-modules with unattractive designs so that students are reluctant to read material that does not have developments that attract students' interest in reading. Therefore, it is necessary to develop a debate text e-module using a critical thinking strategy that combines the direct learning process through face-to-face and online learning with an attractive e-module design quality and increases students' reading interest. The results of this study indicate that the learning model that have been developed can be categorized as “Very Eligible”. This is evidenced by the average score of 89. The average score obtained from material experts is 85, from media experts is 96, and from teaching experts is 87. 85. Based on this, it can be concluded that the e-development design Debate text module through critical thinking strategy In SMA Class X is feasible to be implemented, it is expected to be a supplement in learning so that students are more active and independent.